Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1103/physrevlett.82.2548
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Optical Limiting Behavior of Carbon Nanotubes

Abstract: Carbon nanotubes prepared by catalytic (CO) disproportionation were studied using TEM, XRD, UPS, XPS, and optical spectroscopies. In comparison with graphite, the carbon nanotubes show greater interplanar distance, smaller work function, steeper Fermi edge, negative core-level shift, and stronger plasma excitation. Their valence band is basically the same as that of graphite, with lower intensity in the binding energy region of 2-7 eV. The carbon nanotubes exhibit a strong optical limiting effect, superior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
241
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(260 citation statements)
references
References 17 publications
15
241
0
1
Order By: Relevance
“…This broad band results from σ +π excitations and is centred around 27.0 eV for samples prepared with wall temperatures of 100 and 80 • C and at a slightly lower energy of ∼25 eV for T wall = 60 • C. These loss features are typical of graphite-like structures, like carbon nanotubes [32][33][34]. Peaks at ∼6 eV are attributed to π -π* collective excitations.…”
Section: Xps Analysismentioning
confidence: 97%
“…This broad band results from σ +π excitations and is centred around 27.0 eV for samples prepared with wall temperatures of 100 and 80 • C and at a slightly lower energy of ∼25 eV for T wall = 60 • C. These loss features are typical of graphite-like structures, like carbon nanotubes [32][33][34]. Peaks at ∼6 eV are attributed to π -π* collective excitations.…”
Section: Xps Analysismentioning
confidence: 97%
“…Au has a work function of ϳ5.3 eV, whereas nanotubes were found to have a work function of about 4.3 eV. 24,25 The aligning of the Fermi levels by transfer of electrons from nanotube to gold leads to an asymmetric position of the nanotube band structure relative to the Fermi level. From the STS spectra we find that ‫ץ‬E is about 0.3Ϯ0.1 eV for both metallic and semiconducting nanotubes, independent of ⌬E gap and ⌬E sub .…”
Section: Long Nanotubesmentioning
confidence: 99%
“…23 Chen et al observed that the optical transmission in CNTs in ethanol at 532 and 1064 nm is reduced for smaller power levels than for carbon black in distilled water. 24 This has been attributed to stronger plasma excitations for carbon nanotubes. The optical absorption of CNT and graphite in the considered wavelength interval ͑640-480 nm͒ is similar and increases monotonously with decreasing wavelength.…”
mentioning
confidence: 99%